PCIF1 catalyzes m6Am mRNA methylation to regulate gene expression - Sendinc, E; Valle-Garcia, D; Dhall, A; Chen, H; Henriques, T; Navarrete-Perea, J; Sheng, W; Gygi, SP; Adelman, K; Shi, Y (Elsevier, 2019)
mRNA modifications play important roles in regulating gene expression. One of the most abundant mRNA modifications is N6,2-O-dimethyladenosine (m6Am). Here, we demonstrate that m6Am is an evolutionarily conserved mRNA modification mediated by the Phosphorylated CTD Interacting Factor 1 (PCIF1), which catalyzes m6A methylation on 2-O-methylated adenine located at the 5′ ends of mRNAs. Furthermore, PCIF1 catalyzes only 5′ m6Am methylation of capped mRNAs but not internal m6A methylation in vitro and in vivo. To study the biological role of m6Am, we developed a robust methodology (m6Am-Exo-Seq) to map its transcriptome-wide distribution, which revealed no global crosstalk between m6Am and m6A under assayed conditions, suggesting that m6Am is functionally distinct from m6A. Importantly, we find that m6Am does not alter mRNA transcription or stability but negatively impacts cap-dependent translation of methylated mRNAs. Together, we identify the only human mRNA m6Am methyltransferase and demonstrate a mechanism of gene expression regulation through PCIF1-mediated m6Am mRNA methylation.